The Impact of Change to Components of Composite Index on the Affected Stocks - Lu, Ming Pey (2010)
Based on the belief that stock market performance should reflect stock liquidity, Bursa Malaysia (BM) works with Financial Times Stock Exchange (FTSE) to introduce a new market index, known as FTSE-BM30 or FBM30, to replace Kuala Lumpur Composite Index (KLCI). With the introduction of FBM30 on 6th July, 2009, KLCI was discontinued. FBM30 is composed of 30 blue chip stocks while KLCI is made up of 100 stocks. With the introduction of a new index with smaller number of stocks, at least 70 stocks that were previously used to calculate KLCI have to be dropped. The purpose of this study is to look at investors' reactions to the actual introduction of FBM30 on 6th July, 2009 on the prices of three stocks that are newly included into FBM30, 27 stocks from KLCI that remained in FBM30, and 73 stocks from KLCI that are dropped from FBM30. Using event study methodology, the findings reveal that companies that are newly included into and companies that remain in FBM30 have insignificant abnormal return. However, for the companies that are dropped from KLCI experienced significant abnormal negative return when FBM30 comes into effect.